1981
DOI: 10.1136/adc.56.10.787
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of a new device for delivering aerosol drugs to asthmatic children.

Abstract: SUMMARY A new device, known as the aerochamber, for delivering aerosol drugs was compared with a standard aerosol inhaler in asthmatic children aged between 5 years 3 months and 13 years 10 months. The study was conducted under doubleblind conditions using fenoterol, a 3 2 stimulant, as the active agent and a placebo. Response to treatment was assessed by measuring the peak expiratory flow rate before and after each inhaler. Seven of 10 children had greater mean improvements in peak expiratory flow rates when … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0
1

Year Published

1984
1984
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(3 citation statements)
references
References 5 publications
0
2
0
1
Order By: Relevance
“…In another adult study, 26 it was reported that patients who are "unable to use a pressurized aerosol efficiently" will achieve greater improvement in pulmonary function using terbutaline with a tube spacer vs an MDI alone. Although most clinical evaluations of spacer devices have found that the response to short-acting ␤ 2 -agonists is equivalent to that achieved with correctly performed MDI technique, [15][16][17][18][19][20][21][22][23] one pediatric study found that the MDI plus a 750-mL spacer was superior to correct use of MDI alone. 31 One adult study of primarily chronic bronchitis patients also showed that a spacer device provided a better response to a short-acting ␤ 2 -agonist.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In another adult study, 26 it was reported that patients who are "unable to use a pressurized aerosol efficiently" will achieve greater improvement in pulmonary function using terbutaline with a tube spacer vs an MDI alone. Although most clinical evaluations of spacer devices have found that the response to short-acting ␤ 2 -agonists is equivalent to that achieved with correctly performed MDI technique, [15][16][17][18][19][20][21][22][23] one pediatric study found that the MDI plus a 750-mL spacer was superior to correct use of MDI alone. 31 One adult study of primarily chronic bronchitis patients also showed that a spacer device provided a better response to a short-acting ␤ 2 -agonist.…”
Section: Discussionmentioning
confidence: 99%
“…5 Numerous trials have demonstrated that a large percentage of patients make errors in using MDI, 6 -11 and evaluations of health professionals reveal similar difficulties. [12][13][14] Studies have shown that spacer devices provide at least equivalent efficacy in patients with optimal MDI technique, [15][16][17][18][19][20][21][22][23] and enhance efficacy of short-acting ␤ 2 -agonists in stable patients who have poor MDI technique. [23][24][25][26] Our review of the literature shows no studies comparing salmeterol MDI alone with salmeterol MDI plus a delivery-enhancement or spacer device.…”
mentioning
confidence: 99%
“…La tecnica de inhalation es particularmente importance en nifios de corta edad 11 -12 , en quienes la principal dificultad consiste en sincronizar la inhalation con la descarga, como ocurre con elempleo de dosificadores apresion 13 ' 14 -Varies autores han propuesto diferentes adaptaciones como bolsas colapsables 15 -16 , tubos de extension bucal 12 ' 17 , aerocamaras 13 -18 -19 , las que no siempre resultan efectjvas pues requieren Un esfuerzo respiratorio exclusivamente bucal y ademas aumentan los costos.…”
unclassified